A single-stage hybrid (dry/wet) dephlegmator for application in air-cooled steam condensers: Performance analysis and implications - du Plessis, Jacques; Owen, Michael (Thermal science and engineering progress, 2021)
•Dry-cooled condensers have limited performance at high ambient temperatures.•A single stage hybrid dephlegmator is proposed to increase condenser performance.•The hybrid ACC is more compact and therefore less capital intensive.•The average annual water consumption in the hybrid ACC is 0.19 kL/MWh.•The hybrid ACC could also mitigate the adverse effects of wind on conventional ACC performance. This paper presents a comparative simulation between a Rankine cycle steam turbine coupled to a hybrid air-cooled condenser (ACC) which incorporated a single-stage hybrid (dry/wet) dephlegmator (HDWD) and a conventional (all-dry) ACC. The comparative simulation consisted of three scenarios: site-specific design conditions, annual modelling (typical meteorological year), and a hypothetical adverse wind condition case. The hybrid ACC that incorporates an HDWD aim to enhance condenser performance during high ambient temperatures or windy periods by operating in deluge mode. This study showcases the operational benefits of the hybrid ACC and answers important questions regarding the technical feasibility of such a system. In the first scenario, the hybrid (deluge mode) and conventional ACC were sized at the 1% design condition for a minimum number of units while maintaining a turbine backpressure of 19942.7 Pa. The hybrid ACC consisted of 4 streets of 6 units, while the conventional ACC consisted of 6 streets of 6 units. At the design conditions, the hybrid ACC’s specific water evaporation was 0.8kL/MWh and the HDWD’s heat transfer rate was approximately 4.7 times greater than a conventional dephlegmator unit. The second scenario demonstrated that the hybrid ACC could operate in dry mode for 75% of the year (Tdb < 29.72 °C) with an annual specific water consumption of 0.19kL/MWh (significantly less than a wet-cooled plant). The third scenario showed that the hybrid ACC could also mitigate the adverse effects of wind on conventional ACC performance.